Circulating Irisin and Rare Adipokines in Female Metabolic Disorders: Associations with Hormonal Imbalance and Obesity - Jalank Hameed Mahmoud (American Journal of Biology and Natural Sciences, 2026)
Background & Objective: Adipokines are important metabolic regulators; however, their relationship with metabolic and hormonal profiles of women is not completely known. To evaluate irisin, omentin‑1, chemerin, and vaspin in the circulation together with anthropometric, metabolic and endocrine indices among Iraqi females having metabolic disorders. Materials & Methods: Cross-sectional 75 patients and 75 healthy controls were included. The anthropometric measurements, fasting glucose, HbA1c, lipid profiles, HOMA‑IR, adipokines and hormones (estrogen, testosterone, LH and FSH TSH T3 and T4) were determined with standard protocols and commercially available ELISA kits(Sunlong Co., China; Biobase Analyzer). Results: Clinical investigation showed a significantly higher BMI and waist-to-hip ratio in patients versus controls. Metabolic profiling revealed significant higher fasting glucose (105.6 ± 14.2 vs. 92.1 ± 8.5 mg/dL), HbA1c (5.9 ± 0.7 vs. 5.1 ± 0,4%), and HOMA-IR (2,8 ± 1,1 vs.15 ±,6; p <0,001). In addition, a dyslipidemic profile was observed among the patients with significantly higher total cholesterol (TC), LDL and TGs along with lower HDL (p < 0.001). With respect to adipokines, patients revealed significantly decreased concentrations of Irisin and Omentin-1 in comparison with increased levels of Chemerin and Vaspin (p < 0.001). Biochemical analyses demonstrated marked increases in Testosterone, LH and TSH levels (p < 0.05) and a significant decrease of Estrogen. No large deviation was detected for FSH, T3 and T4. Conclusions: Women with metabolic dysfunction exhibit obesity, insulin resistance, dyslipidemia and mild endocrine unbalance, associated with significant adipokine dysregulation: low irisin and omentin‑1 and high chemerin and vaspin levels can be considered as possible candidates for early biomarkers.